1995
DOI: 10.1164/ajrccm.151.5.7735580
|View full text |Cite
|
Sign up to set email alerts
|

Which index of peak expiratory flow is most useful in the management of stable asthma?

Abstract: Calculation of diurnal peak expiratory flow (PEF) variability using values before and after bronchodilator is no longer possible for many asthmatic patients because they now use beta-agonists "as needed" for symptoms rather than regularly. This study assesses the usefulness of a number of alternative PEF indices as markers of airway liability in subjects with stable, although not necessarily well-controlled, asthma. Forty-six adult subjects completed a questionnaire about symptoms and treatment in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
2
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 25 publications
4
76
2
2
Order By: Relevance
“…Thus, improvement through training extended beyond patients' perception of their disease to a somatic outcome measure central to the pathophysiology of asthma. Although the relationship between PEF variability and airway hyperresponsiveness has been debated (Douma, Kerstjens, Roos, et al, 2000;Reddel, Salome, Peat, et al, 1995), such findings are compatible with prior findings of a negative correlation between pCO 2 and hyperresponsiveness to methacholine challenge (Osborne et al, 2000). It is likely that additional benefits of an adjunctive breathing training will be less apparent in basal lung function (or only be visible in more direct measures of airway obstruction) than in a reduction of fluctuations in symptoms.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, improvement through training extended beyond patients' perception of their disease to a somatic outcome measure central to the pathophysiology of asthma. Although the relationship between PEF variability and airway hyperresponsiveness has been debated (Douma, Kerstjens, Roos, et al, 2000;Reddel, Salome, Peat, et al, 1995), such findings are compatible with prior findings of a negative correlation between pCO 2 and hyperresponsiveness to methacholine challenge (Osborne et al, 2000). It is likely that additional benefits of an adjunctive breathing training will be less apparent in basal lung function (or only be visible in more direct measures of airway obstruction) than in a reduction of fluctuations in symptoms.…”
Section: Discussionsupporting
confidence: 76%
“…We used morning PEF since Reddel et al (12) showed that the minimum morning prebronchodilator PEF over a week was the most useful index in the management of asthma. In addition, morning measurements of PEF had a smaller number of missing points in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies showed that diurnal variability correlated well with BHR [7,19]. REDDEL et al [8] recommended minimum pre-BD PEFa.m. (%recent best) as the most useful index, because it strongly correlates with BHR in patients with stable asthma and does not require the use of BDs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PEF variation is thought by many experts to reflect the degree of bronchial hyperresponsiveness (BHR) [6]. Several cross-sectional studies have indeed shown moderate-to-strong correlations between PEF indices and BHR [2,7,8]. However, if serial PEF measurements are to be used in patients to reflect BHR in order to monitor asthma severity, the measure of PEF variation should correlate with changes in BHR within patients longitudinally, instead of between patients cross-sectionally.…”
mentioning
confidence: 99%
See 1 more Smart Citation